Effect of Nicotinamide Against Candida albicans - Xing, XinRui; Liao, ZeBin; Tan, Fei; Zhu, ZhenYu; Jiang, Yuanying; Cao, YingYing (Frontiers in Microbiology, 2019)
Nicotinamide (NAM) has a long history in clinical applications and can be safely used for treating various diseases. In recent years, NAM was found to exhibit antimicrobial activities, inhibiting the growth of Plasmodium falciparum, Mycobacterium tuberculosis and human immunodeficiency virus (HIV). Here we investigated the activity of NAM against Candida albicans, one of the most prevalent human fungal pathogens. Our results showed that NAM exhibited significant antifungal activity against C. albicans, including fluconazole-resistant isolates. NAM could also effectively suppress biofilm formation. In addition, NAM exhibited antifungal activity against non-Candida albicans species and Cryptococcus neoformans. Combination of NAM and fluconazole showed an even strong antifungal activity. The antifungal activity of NAM was further confirmed in a mouse model of disseminated candidiasis. Confocal laser scanning microscopy revealed that NAM increased cell wall β-glucans exposure and chitin content while decreased mannan level. Furthermore, by screening the C. albicans homozygous deletion mutant library, the C. albicans mutant lacking GIN4, which encodes a septin regulatory protein kinase and is essential for the maintenance of cell wall integrity, was identified to be high sensitive to NAM. These findings suggested that NAM might exhibit antifungal activities through affecting cell wall organization.